Handling of Illegal Fishing Based on Legal Perspectives in Indonesia - Fauziyah, Fauziyah; Rizkina, Fitriana Dina; Wahyudi, Ahmad Rihnu Erzal (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 3 (2024), 2024)
Indonesia becomes the source of illegal, unreported, unregulated fishing (IUUF) since it is a maritime nation with an estimated 9.9 million tons of fish resources per year. Indonesia forbids IUUF because it violates requirements of the Indonesian Law Number 45 of 2009, the Indonesian Law Number 32 of 2014, and the 1982 United Nations Convention on the Law of the Sea. Sectoral egos amongst domestic institutions, however, are currently impeding the exchange of data and information concerning IUUF, which is hindering the overcoming of IUUF. Thus, the Control Center of Task Force 115, which has the responsibility for organizing interoperability, can be used to build a solution for data and information exchange by creating a platform that can integrate various domestic institutions' facilities into a single data and information center. Then, through the reconstruction of Ministerial Regulation Number 37/PERMEN-KP/2017, the execution of interoperability is described in a regulation. This solution must be implemented to avoid duplication of authority among domestic institutions and the inefficiency of Task Force 115's Control Center's role as the coordinator of the exchange of surveillance data or information about IUUF actors who will or have entered the Indonesian Sea.